Construction regulations along metro alignment - Ghiasi, Vahed; Omar, Husaini; Rostami, Jamal; Kim Huat, Bujang (American-Eurasian Network for Scientific Information, 2010)
The purpose of the current study was to determine construction regulations along subway alignment. The study aims to expand the underground tunnelling technique, comparison of different tunnel excavation techniques, tunnelling machines. The aim of this study was to evaluate and validate construction hazards and mitigation measures, shafts sinking, tunnel, excavated material determination. In recent years, there has been an increasing interest in subway construction. The paper opted for an exploratory study using different method for metro tunnel construction regulation. In this paper we argue about tunnel and station compatibility, TBM drive before station construction, TBM drive after station construction, construction cost and duration comparison for different tunnel construction techniques, segment plant design, segment structural design, dump site, safety factors, affecting the segment plant design are some approach to achieve construction regulations along subway alignment. One of the more significant findings to emerge from this study is that this paper is so useful for tunnel designer and also the paper provides tunnelling methods, ground and underground conditions, methods of support and stabilizations, tunnelling machine, advantages and disadvantages of methods and materials are discussed. The current investigation was limited by empirical method for construction tunnel alignments. Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to update the proposed propositions further. The implications of the anticipated ground conditions on machine and ground support selection as well as the field observation of the actual conditions will be discussed in this paper. Designing tunnels and subway stations are usually based on underground investigations. More broadly, the paper includes implications for the development of tunnels and underground designing also designers need to determine standards and coeds. This study is a precise and concise construction regulation along metro alignment. The present study confirms previous findings and contributes additional evidence that suggests that there are many studies conducted using laboratory and field test results for tunnel structures. This paper fulfils an identified need to study construction regulations along metro alignment can be enabled.